2013
DOI: 10.1111/pme.12133
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Parameters Do Not Correlate with Pain Intensity in Healthy Volunteers

Abstract: HRV parameters may detect responses to heat pain, but are not suitable to assess pain intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…In humans, heart-related pain is associated with a reduction in HRV, suggesting that cardiac pain shifts the autonomic balance toward the sympathetic dominance (Ruggeri et al, 1996). Similarly, Yap et al (2000) found that the sympathovagal balance shifts toward sympathetic dominance when the HRV is reduced; SDNN is also decreased in humans subjected to pain (Meeuse et al, 2013). In summary, these results suggest that pain is greater during rectal palpation with uterine palpation compared with rectal palpation without uterine palpation in both healthy and metritic cows.…”
Section: Hrv During Rectal Palpation With and Without Uterine Palpationmentioning
confidence: 82%
“…In humans, heart-related pain is associated with a reduction in HRV, suggesting that cardiac pain shifts the autonomic balance toward the sympathetic dominance (Ruggeri et al, 1996). Similarly, Yap et al (2000) found that the sympathovagal balance shifts toward sympathetic dominance when the HRV is reduced; SDNN is also decreased in humans subjected to pain (Meeuse et al, 2013). In summary, these results suggest that pain is greater during rectal palpation with uterine palpation compared with rectal palpation without uterine palpation in both healthy and metritic cows.…”
Section: Hrv During Rectal Palpation With and Without Uterine Palpationmentioning
confidence: 82%
“…Fluctuations in heart rate during breathing cycles (respiratory sinus arrhythmia) have been integrated to improve parameter accuracy . It is thought to be influenced by noxious stimuli, particularly under steady‐state anaesthesia, but translation into non‐anaesthetised patients is contentious, along with the correlation between heart rate variability and pain intensity . Both pre‐clinical studies and recent clinical trials suggest it could be developed in future into an objective pain assessment tool .…”
Section: Resultsmentioning
confidence: 99%
“…While some may argue that nurses are able to discern stress, fear, and other emotional responses to being ill and voiceless through blood pressure, heart rate, and respiratory factors (Vaajoki, Kankkunen, Pietil€ a, & Vehvil€ ainen-Julkunen, 2011) as well as facial cueing (Molony, Kobayashi, Holleran, & Mezy, 2005), it is suspected that these inferences actually may be inaccurate. In a study of 75 healthy subjects during three periods of application of painful stimulus lasting for 2 minutes, Meeuse et al (2013) found that there was no correlation between painful stimulus and heart rate variability. They also noted there were no changes in respiratory rate with the application of painful stimuli.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In a study of 75 healthy subjects during three periods of application of painful stimulus lasting for 2 minutes, Meeuse et al. () found that there was no correlation between painful stimulus and heart rate variability. They also noted there were no changes in respiratory rate with the application of painful stimuli.…”
Section: Literature Reviewmentioning
confidence: 99%